Does Local Government Financial Condition Drive Public Sector Innovation? Evidence from Provincial Governments in Indonesia - Iman Teguh; Neni Nurhayati (Jurnal Riset Akuntansi Terpadu, 2026)
Public sector innovation (PSI) has become an increasingly critical agenda for local governments, particularly amid growing fiscal constraints and the complexity of societal demands. However, the extent to which local government financial condition, as a socio-economic antecedent of PSI, drives regional innovation remains empirically underexplored, particularly from an accounting perspective. Grounded in an integrated conceptual framework combining demand and supply theory and organizational slack theory, this study aims to examine the influence of local government financial condition on PSI among provincial local governments in Indonesia. Employing an explanatory quantitative approach with panel data, this study uses a sample of 34 provincial local governments in Indonesia covering the period 2021 to 2024. Data were sourced from audited local government financial statements and the regional innovation index reported in the Innovation Government Awards (IGA). The Random Effect Model was selected as the best-fitting estimation model following Chow, Hausman, and Lagrange Multiplier tests. The findings reveal that local government financial condition variables jointly exert a significant influence on PSI, accounting for 22.91% of its variation. However, on a partial basis, only financial independence is proven to have a positive and significant linear effect on PSI, while financial flexibility, operating solvency, long-run solvency, service-level solvency, and short-run solvency are not statistically significant in a linear specification. A supplementary nonlinear (quadratic) test further reveals that operating solvency, and to a lesser extent financial flexibility, exhibit a statistically significant curvilinear (U-shaped) association with PSI, indicating that the slack-innovation relationship in this context departs from the conventional inverted-U prediction. These findings affirm that fiscal autonomy, rather than the mere size or surplus of resources, is the primary driver of regional innovation, while also pointing to a more complex, nonlinear role of resource slack that warrants further theoretical attention.